2004
DOI: 10.1016/s0002-9440(10)63257-9
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocytes Do Not Directly Mediate the Protective Effect of Estrogen on Experimental Autoimmune Encephalomyelitis

Abstract: Gender influences mediated by 17␤-estradiol (E2) have been associated with susceptibility to and severity of autoimmune diseases such as diabetes, arthritis, and multiple sclerosis. In this regard, we have shown that estrogen receptor-␣ (Esr1) is crucial for the protective effect of 17␤-estradiol (E2) in murine experimental autoimmune encephalitis (EAE), an animal model of multiple sclerosis. The expression of estrogen receptors among various immune cells (eg, T and B lymphocytes, antigen-presenting cells) sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 38 publications
3
42
3
Order By: Relevance
“…This suggests that E2's effects on vitamin D metabolism are mediated primarily through ERa and is consistent with observations indicating that immunomodulatory effects of E2 are dependent on ERa signaling (53,73). Expression of both ERs was reported on lymphocytes, and it was recently shown that E2-mediated suppression of certain genes, such as IFN-g and RANTES in the EAE model, is dependent on the presence of ERa (74). These results are consistent with observations showing treatment of EAE with an ERa-selective ligand reduces CNS inflammation, resulting in delayed onset, as well as decreased incidence and severity of disease.…”
Section: Foxp3supporting
confidence: 87%
“…This suggests that E2's effects on vitamin D metabolism are mediated primarily through ERa and is consistent with observations indicating that immunomodulatory effects of E2 are dependent on ERa signaling (53,73). Expression of both ERs was reported on lymphocytes, and it was recently shown that E2-mediated suppression of certain genes, such as IFN-g and RANTES in the EAE model, is dependent on the presence of ERa (74). These results are consistent with observations showing treatment of EAE with an ERa-selective ligand reduces CNS inflammation, resulting in delayed onset, as well as decreased incidence and severity of disease.…”
Section: Foxp3supporting
confidence: 87%
“…Recently, we demonstrated that treatment of EAE with pregnancy levels of estrogen invariably reduced subsequent neurologic disease, in part, through a suppression of T H 1 and T H 17 cell functions and a shift toward T H 2 and T reg cells (Haghmorad et al 2014a). Polanczyk et al (2004) demonstrated that protective effects of estrogen treatment were not mediated through direct action on the encephalitogenic T-cells, and that both immune and CNS cells were required in propagating immunomodulatory effects of E2. The exact molecular mechanisms in mediating regulatory effects of E2 in EAE have not yet been identified; T reg cells are prime immunoregulatory candidates since their numbers were increased by E2 in EAE-protected mice (Polanczyk et al 2007;Wang et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…[17,25] This notion was itself subsequently challenged by experiments suggesting that the protective action of E2 was not mediated directly by E2-responsive T-cells, but rather through indirect effects on other lymphoid cells or nonlymphoid tissues. [27,28] In an adoptive EAE model, it was shown that ERα expression in encephalitogenic T-cells was dispensable for E2-mediated EAE protection. [27] Likewise, we reported that low dose E2-therapy at the time of disease induction blunted acute EAE development in the absence of ERα expression in hematopoietic cells.…”
Section: Evidence That Estrogens Mediate Experimental Autoimmune Encementioning
confidence: 99%
“…[27,28] In an adoptive EAE model, it was shown that ERα expression in encephalitogenic T-cells was dispensable for E2-mediated EAE protection. [27] Likewise, we reported that low dose E2-therapy at the time of disease induction blunted acute EAE development in the absence of ERα expression in hematopoietic cells. [28] In this latter model, however, protection was mainly effective during the acute phase of EAE and was not associated with immunomodulatory effects on autoantigen-specific CD4 T-cell responses in lymphoid organs in vivo.…”
Section: Evidence That Estrogens Mediate Experimental Autoimmune Encementioning
confidence: 99%
See 1 more Smart Citation